Predictors of Mortality in Progressive Fibrosing Interstitial Lung Diseases - Chen, Xianqiu; Guo, Jian; Yu, Dong; Jie, Bing; Zhou, Ying (Frontiers in Pharmacology, 2021)
Background: Progressive fibrosing interstitial lung disease (PF-ILD) and idiopathic pulmonary fibrosis (IPF) share similar progression phenotype but with different pathophysiological mechanism. The purpose of this study was to assess clinical characteristics and outcomes of patients with PF-ILD in a single-center cohort. Methods: Patients with PF-ILD treated in Shanghai Pulmonary Hospital from Jan. 2013 to Dec. 2014 were retrospectively analyzed. Baseline characteristics and clinical outcomes were collected for survival analysis to identifying clinical predictors of mortality. Results: Among 608 patients with ILD, 132 patients met the diagnostic criteria for PF-ILD. In this single-center cohort, there were 51 (38.6%) cases with connective tissue disease-associated interstitial lung disease (CTD-ILD) and 45 (34.1%) with unclassifiable ILDs. During follow-up, 83 patients (62.9%) either died (N = 79, 59.8%) or underwent lung transplantations (N = 4, 3.0%) with a median duration follow-up time of 53.7 months. Kaplan-Meier survival curves revealed that the 1, 3 and 5-years survival of PF-ILD were 90.9, 58.8 and 48.1%, respectively. In addition, the prognosis of patients with PF-ILD was similar to those with IPF, while it was worse than non-PF-ILD ones. Multivariate Cox regression analysis demonstrated that high-resolution computed tomography (HRCT) scores (HR 1.684, 95% CI 1.017–2.788, p = 0.043) and systolic pulmonary artery pressure (SPAP) > 36.5 mmHg (HR 3.619, 95%CI 1.170–11.194, p = 0.026) were independent risk factors for the mortality of PF-ILD. Conclusion: Extent of fibrotic changes on HRCT and pulmonary hypertension were predictors of mortality in patients with PF-ILD.